A hybrid discrete fourier transform based difference set approach for reduction in peak sidelobe level of planar antenna array. Issue 11 (8th September 2022) - Nath, Ganimidi Veerendra; Subhashini, Konidala Ratna
Abstract: This article proposes an analytical technique based on difference sets (DSs) and discrete fourier transform (DFT) for the synthesis of thinned planar antenna arrays. DSs are chosen as a baseline to prove and establish pattern synthesis rules on the peak sidelobe level (PSL), the directivity, and the first null beam width. DFT technique is employed for finding the nonuniform excitations of a planar antenna array. The hybrid DFT based DS method is designed in this article for the antenna array thinning with an objective of reduction in PSL. This method extracts the excitations by simple cyclic shifts from a suitable DS sequence. The results from a wide simulation are illustrated to validate the reliability and accuracy of the proposed method.